Teaching and learning languages through practice with subtitling - Moraes, Gisele Benck de; Brambilla, Edemilson Antônio; Silveira, Mariane Rocha (The ESPecialist, 2024)
This study examines the benefits of subtitling as a digital tool for the learning and teaching of Spanish, as explicit knowledge, from the analysis of extracts translated into Portuguese, using the Subtitle Workshop Digital Platform. Students carried out in-class activities at an undergraduate course at a community university in Rio Grande do Sul. Firstly, the students learnt about and had access to the Digital Platform and some subtitling exercises. During that first contact, instructional intervention counted on a series of pedagogical strategies, namely: explanations, examples and demonstrative activities. Following, they translated a short extract into Portuguese, making adjustments as required by the platform in conformity with the target language. The theoretical framework was drawn from: Arrojo (1992), Ellis (1994, 2001), Díaz Cintas (2003), Mendes (2007), Barbosa (2009), Eco (2011) and Spada (1997). Results show that instructional intervention on the use of subtitling was beneficial to the learning of Spanish, as it brings students in direct contact with the language and what they need to use, in a more explicit manner, in the target language. Moreover, the learners showed and pointed a better understanding of how Spanish can be learnt and taught more creatively and with digital resources.